The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00438-018-1453-2
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing in maya indigenous families: variant in PPP1R3A is associated with type 2 diabetes

Abstract: It has been presumed that increased susceptibility in Mexicans to type 2 diabetes (T2D) is attributed to the Native American genetic ancestry. Nonetheless, it is not known if there are private genetic variants that confer susceptibility to develop T2D in our population. The Maya indigenous group has the highest proportion of Native American ancestry (98%) which makes it a representative group of the original peoples of Mexico. Thus, the aim of the present study is to identify new genetic variants associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Of all mammals, bats offer unique opportunities for studying molecular adaptations associated with diet. As a taxonomic order, they show unparalleled dietary diversity and a suite of physiological and sensory adaptations for the acquisition and processing of food ( Dumont et al 2012 ; Fenton 2013 ; Jones et al 2013 ; McNab 2013 ; Santana and Cheung 2016 ). However, studies of molecular adaptation in metabolism-related genes in bats have been limited in scope, typically focusing on small numbers of genes or, more recently, larger gene sets but in fewer species ( Gutiérrez-Guerrero et al 2020 ; Wang et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of all mammals, bats offer unique opportunities for studying molecular adaptations associated with diet. As a taxonomic order, they show unparalleled dietary diversity and a suite of physiological and sensory adaptations for the acquisition and processing of food ( Dumont et al 2012 ; Fenton 2013 ; Jones et al 2013 ; McNab 2013 ; Santana and Cheung 2016 ). However, studies of molecular adaptation in metabolism-related genes in bats have been limited in scope, typically focusing on small numbers of genes or, more recently, larger gene sets but in fewer species ( Gutiérrez-Guerrero et al 2020 ; Wang et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A third, rather minor QTL on SSC18, contains 21 variants downstream of MDFIC (min p-value 1.97 × 10 −15 ), a gene which has been linked to improved piglet birth weight (Zhang et al 2014). 25 intron and 42 downstream variants were found for the PPP1R3A gene (min p-value 6.92 × 10 −15 ), which in a whole exome sequencing study was found to be associated with type 2 diabetes in a Mayan population (Sánchez-Pozos et al 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Comparative analyses among Mestizos, Natives, and continental populations, highlight the extent of our incomplete registry of pharmacogenetic variability within the country, but also indicate a closer completion for Mestizos than for Natives, because these have been much less studied (Cid-Soto et al, 2018; Sánchez-Pozos et al, 2018). For instance, Natives showed 2.4 functional novel variants on average per individual compared to 0.7 in Mestizos, which is in agreement with Romero-Hidalgo et al (2017) showing that damaging variation is 2× higher for unreported variants in Native Americans.…”
Section: Discussionmentioning
confidence: 99%